منهج أكرم ضياء العمري في الاستشهاد بالقرآن وبروايات السير في السيرة النبوية : دراسة موضوعية - Ahmad Salahuddin M. Azizan (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BA019 1015-1032